Effects of general versus regional anaesthesia on circadian melatonin rhythm and its association with postoperative delirium in elderly patients undergoing hip fracture surgery: study protocol for a prospective cohort clinical trial. Issue 2 (12th February 2021) - Yuan, Yi; Song, Yanan; Wang, Geng; Jia, Yunyang; Zhou, Yang; Mi, Xinning; Jia, Xixi; Wang, Xiaoxiao; Liu, Chang; Li, Yue; Shi, Chengmei; Han, Yongzheng; et al.
Abstract : Introduction: Postoperative delirium (POD) is a common neurological complication after hip fracture surgery and is associated with high morbidity and mortality in elderly patients. Although the specific mechanism of POD remains unclear, circadian rhythm disruptions have recently drawn increased attention. To date, only limited postoperative time points of plasma melatonin level measurements were recorded in previous studies, and such data cannot represent a comprehensive melatonin rhythm. The process of anaesthesia (either general anaesthesia (GA) or regional anaesthesia (RA)) is known to influence the melatonin rhythm. However, how these two anaesthesia methods differently affect the postoperative melatonin rhythm is still unknown. Therefore, we hypothesise that RA may attenuate the disruption of the melatonin rhythm, which might decrease the incidence of POD in elderly patients undergoing hip surgery. Methods and analysis: In this prospective cohort clinical trial, 138 patients scheduled for hip fracture surgery will be divided into two groups to receive either GA or RA. The primary aim is to compare the circadian rhythm of melatonin secretion between the two groups and explore its association with the incidence of POD. Ethics and dissemination: The study has been approved by the Medical Science Research Ethics Committees of Beijing Jishuitan Hospital (JLKS201901-04). The results of the study will be published in peer-reviewed international journals. Trial registration number: ChiCTR1900027393.